Skriven i avsaknadens tecken - Bruno K. Öijer som musans poet - Górecka, Dominika (Folia Scandinavica Posnaniensia, 2007)
The aim of this article is to present Bruno K. Oijer’s (b.1951) poetry as a way of addressing the Muse, and himself as a Muse poet, as defined in Robert Graves’ The White Goddess, wh ich Oijer often referred to in many of his utterances. Numerous references to the book are made in order to shed light on the aspect of mother and child, as well as the poet's return to his birthplace, which are most frequent in his latest collection of poems, the so-called Trilogy. An analysis of Oijer's concept of nature is also conducted, as the feminine particle - in the shape of a deprived Mother Earth - is present even there. My assumption is that Oijer wants to carry on the tradition of a romantic poet who can - if only he remains sincere with himself - read from the great book of nature and decode it for the rest of us. In order to see things clearly, he has to go as far as to stay apart from society, and his poetry becomes a requiem played for our planet, an innocent child's farewell to the Earth as it used to be.